191k views
5 votes
Simplify the following expression, using the order of operations.
8(5-3)3 +9

2 Answers

1 vote
your answer is 57 love!
User Kristiana
by
4.7k points
4 votes

Hi!

Your answer should be: 57

Lets do the problem together.

8(5-3)3+9*

*Note, when numbers are next to brackets and there is no mathematical sign, it means multiply. For ex: (1)4=1x4

First, we start with the parenthesis.

5-3=2

So now, the equation is: 8x2x3+9

Now, we multiply from left to right.

8x2=16

So now, its: 16x3+9

Again, we multiply.

16x3= 48

So now, its 48+9

48+9=57

___________

8(5-3)3+9

=8x2x3+9

=16x3+9

=48+9

=57

___________

Hope this helps!

Let me know if you need anymore help, id be delighted to!

Yours truly,

~~~PicklePoppers~~~

User VladoDemcak
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.